PENGARUH HIGH PERFOMANCE WORK SYSTEM DAN WORK ENGAGEMENT TERHADAP EMPLOYEE CREATIVITY DENGAN WORK WELL BEING SEBAGAI PEMEDIASI - FATIN FADILA; ZULFA ULIANI (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2020)
ABSTRACTThis study aims to examine the effect of high performance work system (HPWS) and work engagement on employee creativity with work well-being as a mediator. This study uses quantitative methods by using primary data in collecting data obtained by distributing online questionnaires with google form. The number of respondents in this study were 80 respondents who worked in Solo Raya (Sukoharjo, Wonogiri, Karanganyar, Klaten, Boyolali). The data analysis technique used linear regression analysis using SPSS 22 software in processing the data. The results showed that the high-performance work system (HPWS) had a significant positive effect on work well-being. Work engagement has a significant positive effect on work well-being. High performance work system (HPWS) has a significant positive effect on employee creativity through work well-being as a mediator. Work well-being has a significant positive effect on employee creativity.Keywords: High Performance Work System (HPWS), Work Engagement, Employees Creativity, Work Well-Being.ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh high performance work system (HPWS) dan work engagement terhadap employee creativity dengan work well-being sebagai pemediasi. Penelitian ini menggunakan metode kuantitaif dengan menggunakan data primer dalam pengambilan data yang diperoleh dengan cara menyebarkan kuesioner secara online melalui google form. Jumlah responden dalam penelitian ini sebanyak 80 responden yang bekerja di Solo Raya (Sukoharjo, Wonogiri, Karanganyar, Klaten, Boyolali). Teknik analisis data menggunakan analisis regresi linier dengan menggunakan software SPSS 22 dalam mengolah data. Hasil penelitian menunjukkan bahwa high performance work system (HPWS) berpengaruh signifikan positif terhadap work well- being. Work engagement berpengaruh signifikan positif terhadap work well-being. High performance work system (HPWS) berpengaruh signifikan positif terhadap employee creativity melalui work well- being sebagai pemediasi. Work well-being berpengaruh signifikan positif terhadap employee creativity.Kata kunci: High Performance Work System (HPWS), Work Engagement, Employee Creativity, Work Well-Being.